2006
DOI: 10.1007/bf02974079
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofNelumbinis semen on contractile dysfunction in ischemic and reperfused rat heart

Abstract: Nelumbinis Semen (NS), or lotus seed, is one of the most well-known traditional herbal medicines and is frequently used to treat cardiovascular symptoms in Korea. The anti-ischemic effects of NS on ischemia-induced isolated rat heart were investigated through analyses of changes in blood pressure, aortic flow, coronary flow, and cardiac output. The subjects in this study were divided into two groups: a control, untreated ischemia-induced group, and an ischemia-induced group treated with NS. There were no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Studies on different parts of N. nucifera have shown a variety of pharmacological activities. Extracts of different parts have shown anti‐ischaemia, 13 antioxidant, 14–19 anticancer, 5,11 antiviral, 20,21 anti‐obesity, 22 lipolytic, 23 hypocholesterolaemic, 24 antipyretic, 25 hepatoprotective, 26 hypoglycaemic, antidiarrhoeal, antifungal, antibacterial, anti‐inflammatory and diuretic activities 8,27–34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on different parts of N. nucifera have shown a variety of pharmacological activities. Extracts of different parts have shown anti‐ischaemia, 13 antioxidant, 14–19 anticancer, 5,11 antiviral, 20,21 anti‐obesity, 22 lipolytic, 23 hypocholesterolaemic, 24 antipyretic, 25 hepatoprotective, 26 hypoglycaemic, antidiarrhoeal, antifungal, antibacterial, anti‐inflammatory and diuretic activities 8,27–34 …”
Section: Introductionmentioning
confidence: 99%
“…Maximal recovery was seen at a dose of 10 mg/ml, although cardiac output was similar after treatment with 3 or 10 mg/ml doses (63.5 ± 3.2 and 65.8 ± 4.0 ml/min, respectively). Thus, the 3 mg/ml dose was determined to be the optimum dose for anti‐ischaemic effects in the rat 13 …”
Section: Introductionmentioning
confidence: 99%
“…hypoglycaemic, antidiarrhoeal, antimicrobial, diuretic, antipyretic, psychopharmacological, antiinflammatory activities (Mukherjee et al, 1995a(Mukherjee et al, ,b,c,d, 1996a(Mukherjee et al, ,b,c, 1997. Seed of the plant also proved to have several therapeutic potential including anti-ischemic (Kim et al, 2006), antioxidant , hepatoprotective (Sohn et al, 2003), antiproliferative (Liu et al, 2004), anti-inflammatory (Lin et al, 2006) activity. It has been reported that this plant has contain betulinic acid, a steroidal pentacyclic triterpenoid, as one of the phytomolecule which has proved to be a potent lead for several pharmacological activities like anti-inflammatory, anti-tumor, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the 3 mg/ml dose was determined to be the optimum dose for anti-ischaemic effects in the rat. [13]…”
Section: Phytochemistrymentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Studies on different parts of N. nucifera have shown a variety of pharmacological activities. Extracts of different parts have shown anti-ischaemia, [13] antioxidant, [14][15][16][17][18][19] anticancer, [5,11] antiviral, [20,21] anti-obesity, [22] lipolytic, [23] hypocholesterolaemic, [24] antipyretic, [25] hepatoprotective, [26] hypoglycaemic, antidiarrhoeal, antifungal, antibacterial, anti-inflammatory and diuretic activities. [8,[27][28][29][30][31][32][33][34] This article reviews the traditional uses, phytochemistry and therapeutic reports on different part of N. nucifera viz.…”
Section: Introductionmentioning
confidence: 99%